2017
DOI: 10.3390/rs9070733
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Remote Sensing of Snowmelt in a Diverse High-Arctic Tundra Environment Using Time-Lapse Imagery

Abstract: Snow cover is one of the crucial factors influencing the plant distribution in harsh Arctic regions. In tundra environments, wind redistribution of snow leads to a very heterogeneous spatial distribution which influences growth conditions for plants. Therefore, relationships between snow cover and vegetation should be analyzed spatially. In this study, we correlate spatial data sets on tundra vegetation types with snow cover information obtained from orthorectification and classification of images collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 59 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…The temporal dynamics of vegetation across Arctic latitudes and continents could provide essential information for understanding the processes driving current tundra greening/browning patterns, as well as being able to predict future trends. Vegetation changes affect land‐surface albedo, permafrost thaw, animal migration patterns, carbon sequestration, human activities, and more (e.g., Fauchald et al, ; Frost et al, ; Horstkotte et al, ; Kępski et al, ). This study has identified (1) the dynamic patterns of arctic tundra vegetation and (2) the degree to which summer warmth drives tundra vegetation change, and results will provide inputs to analyses that evaluate vegetation change effects on other tundra properties.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal dynamics of vegetation across Arctic latitudes and continents could provide essential information for understanding the processes driving current tundra greening/browning patterns, as well as being able to predict future trends. Vegetation changes affect land‐surface albedo, permafrost thaw, animal migration patterns, carbon sequestration, human activities, and more (e.g., Fauchald et al, ; Frost et al, ; Horstkotte et al, ; Kępski et al, ). This study has identified (1) the dynamic patterns of arctic tundra vegetation and (2) the degree to which summer warmth drives tundra vegetation change, and results will provide inputs to analyses that evaluate vegetation change effects on other tundra properties.…”
Section: Discussionmentioning
confidence: 99%
“…In the absense of measured field data, recent developments in remote sensing may provide new methods of data assimilation. Such methods have already been used in modelling snowmelt-dominated alpine catchments (Bach, Braun, Lampart, & Mauser, 2003) and estimating snowmelt in Arctic tundra (Kepski et al, 2017).…”
Section: Estimating Water Ages and Tt In Data Sparse Arctic Regionsmentioning
confidence: 99%
“…From this perspective, the availability of webcam networks is an important data source for calibration and validation processes. The attention of the scientific community of this proxy is increasing, and the literature about this topic is growing [9,[14][15][16][17]. Furthermore, several tools (for example, FMIPROT and PRACTISE) can be considered for research purposes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%